Synthesis of a novel building block for the preparation of multi-chromophoric sensitizers for panchromatic dye-sensitized solar cells. (January 2017) - Watson, Brian L.; Moore, Thomas A.; Moore, Ana L.; Gust, Devens
Abstract: A simple 3-step synthesis of a novel pyrazine-containing heteroaromatic building block for use as a scaffold for producing multi-chromophoric sensitizers for use in dye sensitized solar cells has been developed. This moiety features two esterified carboxylic acid groups whose hydrolysis provides moieties for anchoring to nanoparticulate metal oxides and two bromine atoms that facilitate attachment of chromophores via palladium mediated cross-coupling methods. The utility of the building block for the synthesis of complex dye motifs is demonstrated by the preparation of a novel panchromatic dye featuring a BODIPY chromophore and a strongly electron donating porphyrin chromophore using both Suzuki and copper-free Sonogashira cross-coupling methods. The building block could be used either to attach two different or identical dye moieties to the metal oxide, or to attach an electron injection dye plus an auxiliary absorber, photoprotective agent, secondary redox moiety, etc. Graphical abstract: Highlights: New synthesis for a linker that attaches dyes to metal oxides for dye sensitized solar cells. Two carboxylic acid groups provide strong binding to the metal oxide. Linker can bind two dyes, which can be the same or different. Linker could bind a dye and an auxiliary pigment or photoprotective agent.